COVERAGE OF ENVIRONMENTAL TOPICS IN PRINT MEDIA (THE EXPERIENCE OF UZBEKISTAN) - qizi, Amirova Madinaxon Hasan (Research Focus International Scientific Journal, 2026)
This article examines the characteristics of coverage of environmental issues through print media (newspapers and magazines) in the Republic of Uzbekistan. The study analyzes how current important environmental topics in Uzbekistan are presented in print mass media. The work includes a content and normative analysis of journal and newspaper materials from 2020 to 2024. According to the results, environmental topics occupy a problematic place in Uzbek print publications, and specialized publications in this field are insufficient. The article provides recommendations aimed at increasing ecological literacy and public awareness.